Changing identity: Retiring from unemployment - Clemens Hetschko; Andreas Knabe; Ronnie Schöb (Freie Universität Berlin, Fachbereich Wirtschaftswissenschaft, 2011)
Using data from the German Socio-Economic Panel from 1984-2009, we follow persons from their working life into their retirement years and find that, on average, employed people maintain their life satisfaction upon retirement, while long-term unemployed people report a substantial increase in their life satisfaction when they retire. These results are robust to controlling for changes in other life circumstances and suggest that retiring is associated with a switch in the relevant social norms that causes an increase in identity utility for the formerly unemployed. This is supportive of the idea that, by including identity in the utility function, results from the empirical life satisfaction literature can be reconciled with the economic theory of individual utility.
Keywords: I31; J26; 330; life satisfaction; retirement; unemployment; identity; social norm; Altersgrenze; Zufriedenheit; Arbeitslosigkeit; Erwerbsverlauf; Persönlichkeitspsychologie; Soziale Norm; Deutschland